KECERDASAN SPIRITUAL SEBAGAI PEMODERASI PENGARUH LOCUS OF CONTROL INTERNAL DAN GAJI AUDITOR PADA KINERJA AUDITOR - Santikawati, Anak Agung Putri; Herkulanus, Bambang Suprasto (E-Jurnal Akuntansi, 2016)
This study aims to investigate the influence of internal locus of control and payroll auditor in the performance of auditors with spiritual intelligence as a moderating variable. This research was conducted on a public accounting firm in Bali in 2016. The number of samples taken 63 auditors who are willing to participate in this study. The sample in this research was determined by purposive sampling method. Data were collected using a survey method. Data analysis technique used is multiple linear regression analysis and Moderated Regression Analysis (MRA). This study successfully demonstrated the internal locus of control and payroll auditor positive effect on the performance of auditors. This study also shows the relationship of spiritual intelligence strengthen internal locus of control on the performance of auditors. The test results by the spiritual intelligence moderation between auditor salary showed spiritual intelligence means to weaken the relationship between payroll auditor in the performance of auditors.
Keywords: Spiritual Intelligence, Internal Locus Of Control, Payroll Auditor, Auditor Performance